Measurement and evaluation of whole body vibration of agricultural tractor operator - Kabir, Md. Shaha Nur; Chung, Sun-Ok; Kim, Yong-Joo; Sung, Nam-Seok; Hong, Soon-Jung (International Journal of Agricultural and Biological Engineering, 2017)
Exposure of whole body vibration (WBV) influences performance, comfort, and long term health risks of tractor operator. Therefore, measurement and evaluation of WBV parameters should be carried out to find probable effects on the health of tractor operators. In this study, a system was designed to measure the WBV of agricultural tractor operators and evaluated the hazard risks on operator’s body according to the ISO standards, and implementation of the WBV test in the official testing station was also suggested. A tri-axial accelerometer was employed to measure vibrations transmitted to the seated operator body as a whole through the supporting surface of the buttock on four typical farm roads under different speeds. The vector sum A(8) exposures on the rough tracks (earthen and grassland roads) exceeded the action limits of 0.5 m/s2 at a 10.9 km/h forward speed and reached to the action limit value at a 16.0 km/h forward speed on the concrete road. The vector sum of VDV(8) exposures did not exceed the action limits of 9.1 m/s1.75 and was greater on the grassland road. The vector sum Sed(8) exposures values exceeded the moderate probability of an adverse health limit of 0.5 MPa on all farm roads at high forward speeds and exceeded the high probability of an adverse health limit of 0.8 MPa on asphalt, concrete, and grassland roads which should be lower than the exposure limit values as suggested by the ISO and EC standards. The WBV evaluation procedure should be considered for implementation at the official tractor test station, which would response to domestic and international tractor test regulations and improve the market competitiveness.Keywords: agricultural tractor, whole body vibration, tractor operator, driving safety, ride comfort, test standard, health riskDOI: 10.3965/j.ijabe.20171001.2113Citation: Kabir Md S N, Chung S-O, Kim Y-J, Sung N-S, Hong S-J. Measurement and evaluation of whole body vibration of agricultural tractor operator. Int J Agric & Biol Eng, 2017; 10(1): 248–255.